Comparative analysis of legislation governing maintenance check flight of aircraft - Rogers, Matthew (Centre for Law and Society, 2025)
Aviation activity is conducted under the ambit of internationally agreed upon Air Law, which imposes the International Civil Aviation Organisation (ICAO)'s Standards and Recommended Practices upon global aviation stakeholders. The imposition of standardised Air Law is in line with ICAO's founding charter, which declares the principles of regulatory uniformity and safety as fundamental postulates. While ICAO's efforts at the standardisation of Air Law are commendable, certain aviation activities occur in the absence of agreed-upon international standards. The Maintenance Check Flight (MCF) is one such activity. An MCF supports the aircraft maintenance process by verifying aircraft system operability after the completion of a maintenance task, or as a troubleshooting step before corrective maintenance action. MCFs are considered more risky than regular commercial flights,1 with several accidents on record which are attributable to the MCF process.2 Despite the elevated risk associated with MCF, there exist notable inconsistencies in MCF regulation across international aviation legal systems. This inconsistent regulatory stasis appears to be at odds with ICAO's fundamental principles, and prompts a compelling research question: what legislative framework exists to promote safety during MCF activity across different legal systems? This study analyses the practical aspects pertaining to MCFs, as well as South African and European Aviation Safety Agency (EASA) jurisprudence to determine the basis of MCF risk, and whether this risk may be managed by exacting Air Law.